Stability and reliability of LTCC-based 5/12 ​V dual output DC-DC converter with high efficiency and small size. (December 2020) - Jung, Dong Yun; Jang, Hyun Gyu; Cho, Doohyung; Park, Kun Sik; Lim, Jong-Won; Lee, Yong Ha; Son, Seok-Ho
Abstract: We propose a 5/12 ​V dual output DC-DC converter that can achieve high efficiency and a small size form factor. Using low temperature co-fired ceramic (LTCC)-based multi-layer circuits, the converter minimizes power losses caused by power and ground metal planes and reduces the size. The lateral dimension of the converter with nine LTCC layers was 35 ​mm ​× ​45 ​mm. The proposed converter was compatible with the outputs of typical electric bike batteries, which are 48 ​V and 36 ​V. At a full-load condition of 3.1 ​A ​at 5 ​V output and 2 ​A ​at 12 ​V output, the measured efficiency was 92.9% and 93.6% with a supply voltage of 48 ​V and 36 ​V, respectively. The measured line regulation with ±20% of an input voltage was lower than 0.75% and load regulation with a 10%–100% load change for the dual output was lower than 1.4%. Under the condition of 100% load for one output and 25%–100% load change for another output, the maximum cross-regulation was 1.7%. The dynamic load regulation and response was lower than 9.6% and 480 μs with 0%–100% load change, respectively, and the maximum ripple and noise was 33.2 mVpp . Reliability tests indicated that the average efficiency degradation rate was less than 0.002%/°C. The results of an electromagnetic interference (EMI) test indicated the converter satisfies the IEC61000-6-3 class B standard. The results show that the LTCC multilayer circuit substrate is suitable for a high-efficiency, high-density, high-output stability, and high-reliability in a power converter.